Caspr2 antibodies in limbic encephalitis with cerebellar ataxia, dyskinesias and myoclonus - Balint, Bettina; Regula, Jens Ulrich; Jarius, Sven; Wildemann, Brigitte (Journal of the neurological sciences, 2013)
Here we report on a case of contactin-associated protein-2 (Caspr2) antibody positive but voltage gated potassium channel (VGKC) antibody negative limbic encephalitis associated with cerebellar ataxia, myoclonus and dyskinesias with favorable response to immunotherapy. This case underlines the importance of Caspr2-specific antibody testing and demonstrates that Caspr2 antibodies are associated with a broader clinical spectrum than hitherto described.